Problem‐solving behaviour of nurses in a lean environment. (6th August 2018) - Gemmel, Paul; Van Beveren, Simon; Landry, Sylvain; Meijboom, Bert
Summary: Aim: To investigate how the extensiveness of a lean implementation—that is, the extent to which lean as a new practice is adopted across nursing departments—relates to second‐order problem solving behaviour of nurses. Background: Lean implementation is expected to stimulate nurses' second‐order problem‐solving behaviour. Method: We used a vignette‐based survey to look for differences in second‐order problem‐solving behaviour in early‐adopter and late‐adopter departments at two hospitals with differing degrees of extensiveness of lean implementation. Results: At the hospital with an extensive lean implementation, nurses at the early‐adopter department showed 71 second‐order problem‐solving responses from 50 problem scenarios, as compared with 39 responses from 37 scenarios in the late‐adopter department. At the hospital with a less extensive lean implementation, these numbers were 16 from 23 compared with 18 from 19. Conclusions: The nurses in the hospital with an extensive lean implementation show more second‐order problem‐solving behaviour than those in the hospital with a stand‐alone approach in a single department. Implications for Nursing Management: Extensive lean implementation where management clearly shows its belief in lean is a more favourable environment for changing the problem‐solving behaviour of nurses.